A cryptocurrency spectrum short analysis - Mircea Constantin Șcheau; Simona Liliana Crăciunescu; Iulia Brici; Monica Violeta Achim (Journal of Risk and Financial Management, 2020)
Technological development brings about economic changes that affect most citizens, both in developed and undeveloped countries. The implementation of blockchain technologies that bring cryptocurrencies into the economy and everyday life also induce risks. Authorities are continuously concerned about ensuring balance, which is, among other things, a prudent attitude. Achieving this goal sometimes requires the development of standards and regulations applicable at the national or global level. This paper attempts to dive deeper into the worldwide operations, related to cryptocurrencies, as part of a general phenomenon, and also expose some of the intersections with cybercrime. Without impeding creativity, implementing suggested proposals must comply with the rules in effect and provide sufficient flexibility for adapting and integrating them. Different segments need to align or reposition, as alteration is only allowed in a positive way. Adopting cryptocurrency decisions should be unitary, based on standard policies.
Keywords: 330; algorithms; blockchain; correlations; cryptocurrencies; fraud; impact; regulation; risks